2012
DOI: 10.1371/journal.pone.0040659
|View full text |Cite
|
Sign up to set email alerts
|

Soil Eukaryotic Microorganism Succession as Affected by Continuous Cropping of Peanut - Pathogenic and Beneficial Fungi were Selected

Abstract: Peanut is an important oil crop worldwide and shows considerable adaptability but growth and yield are negatively affected by continuous cropping. Soil micro-organisms are efficient bio-indicators of soil quality and plant health and are critical to the sustainability of soil-based ecosystem function and to successful plant growth. In this study, 18S rRNA gene clone library analyses were employed to study the succession progress of soil eukaryotic micro-organisms under continuous peanut cultivation. Eight libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
81
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 61 publications
13
81
1
Order By: Relevance
“…It has also been reported that plant pathogens show complex genetic diversities for their different host ranges, pathogenicity and physiological characters, and S. marcescens has the ability to overcome these diversities, which implies that S. marcescens is an ideal bacterium for ecological remediation. Other studies have shown that the soil microbial community is seriously affected by continuous cropping, and the trend toward an increase in pathogens and simplification of the beneficial microorganism community could be an important factor contributing to the decline in peanut growth and yield . Our results of pathogen quantification were in agreement with this.…”
Section: Discussionsupporting
confidence: 91%
“…It has also been reported that plant pathogens show complex genetic diversities for their different host ranges, pathogenicity and physiological characters, and S. marcescens has the ability to overcome these diversities, which implies that S. marcescens is an ideal bacterium for ecological remediation. Other studies have shown that the soil microbial community is seriously affected by continuous cropping, and the trend toward an increase in pathogens and simplification of the beneficial microorganism community could be an important factor contributing to the decline in peanut growth and yield . Our results of pathogen quantification were in agreement with this.…”
Section: Discussionsupporting
confidence: 91%
“…It was reported that the rhizobacterial communities were minor affected by plant development [12], [47]. Interestingly, the eukaryotic microorganisms did not show any obvious correlation with peanut development in the earlier study [23]. There needs to be further study into the interaction mechanisms between microbial communities and the growth or development of peanut.…”
Section: Discussionmentioning
confidence: 75%
“…It was reported that Fusarium genus was major pathogens of plant root rot, and Pseudomonas was major antagonists [40], [41], [42]. Interestingly, contrary to the decrease tendency of Pseudomonales, sequences affiliated with Fusarium showed increasing tendency with continuous cropping of peanut [23], [43]. The succession analyses of soil eukaryotic microorganisms in the earlier study demonstrated that the pathogenic and beneficial fungi were positively selected over time and showed, respectively, increased and simplified tendencies with continuous cropping [23].…”
Section: Discussionmentioning
confidence: 84%
“…As mentioned above, phylotype diversity of fungi also increased during continuous cropping of peanut [5]. Benizri et al [27] reported that the bacterial diversity changed in the continuous cropping soil of peaches.…”
Section: Discussionmentioning
confidence: 99%